Prediction of the invasive level of basal cell carcinomas in the facial area: Analysis of 718 Japanese cases. Issue 3 (September 2020) - Matsushita, Shigeto; Nakamura, Yasuhiro; Tanaka, Ryota; Araki, Ryuichiro; Yamamura, Kentaro; Yoshioka, Manabu; Inoue, Akiha; Komori, Takaya; Saito, Shintaro; Teramoto, Yukiko; Nakamura, Yoshiyuki; Fujisawa, Yasuhiro; et al.
Highlights: Predictors of the invasion level of basal cell carcinomas (BCCs) are unclear. Tumor thickness showed a significant correlation with tumor diameter. Invasion level was significantly correlated with anatomical region and tumor diameter. Our results can help optimize the adequate deep surgical margins in facial BCCs. Abstract: Background: Basal cell carcinoma (BCC) is the most common skin cancer. While Mohs micrographic surgery is commonly accepted for BCC treatment, surgical excision with free margins is widely considered the best treatment modality for BCCs in Japan. However, little is known about the predictors of the invasion levels of BCCs. Objective: To investigate the optimization of deep surgical margins by identifying factors significantly influencing the invasion levels of facial BCCs. Methods: The tumor invasion level was defined as the deepest part of a tumor. Tumor thickness was measured from the top of the granular layer to the deepest extension of the tumor or from the ulcer base overlying the deepest point of invasion in ulcerated lesions. Factors independently associated with tumor thickness and invasion level were identified by multivariate analysis. Six variables were tested: age, sex, anatomical region (nose, orbit, others), histologic pattern (aggressive, non-aggressive), presence of pigmentation, and diameter. Results: We included 718 cases of facial BCCs involving 705 Japanese patients. The most frequent anatomical region and histologic pattern were the nose and nodular pattern, respectively. Only tumor diameter showed a correlation with tumor thickness (β = 0.377, P < 0.001). Tumor diameter (AOR = 71.189, 95 % CI: 11.420–430.931, P = 0.01) and the following anatomical regions showed correlations with the invasion level: nose/others: AOR=2.769, 95 % CI: 1.235–6.493, P = 0.01; orbit/others: AOR=6.369, 95 % CI: 2.728–15.429, P < 0.001; orbit/nose: AOR=2.300, 95 % CI: 1.056–4.984, P = 0.04. Conclusions: This study serves as a guide for optimizing deep surgical margins and planning surgery for facial BCCs considering independently associated factors.